Impact of Epithelial Claudin-4 and Leukotriene B4 Receptor 2 in Normoganglionic Hirschsprung Disease Colon on Post Pull-through Enterocolitis - Abe, Kumpei; Takeda, Masahiro; Ishiyama, Asuka; Shimizu, Masahiro; Goto, Hiroki; Iida, Hisae; Fujimoto, Takashi; Ueda-Abe, Eri; Yamada, Shunsuke; Fujiwara, Kentaro; Shibuya, Soichi; Ochi, Takanori; et al. (Journal of pediatric surgery, 2025)
To investigate whether Leukotriene B4 receptor 2 (BLT-2), an upstream regulator of tight junction protein (TJP) Claudin-4, and TJPs could be etiologic factors in Hirschsprung-associated enterocolitis (HAEC) after pull-through (PT) for Hirschsprung disease (HD). Normoganglionic colon (HD-N) and aganglionic rectum (HD-A) specimens from rectal/rectosigmoid (R/RS) or descending/transverse (D/T) HD were assessed using quantitative polymerase chain reaction (qPCR) for Occludin, TJP-1, TJP-2, Junctional adhesion molecule (JAM)-1, JAM-2, Claudin-1, Claudin-3, Claudin-4, and BLT-2 and immunoblotting for Claudin-4 using fresh specimens obtained intraoperatively (2021–2024; n = 17; R/RS = 15 and D/T = 2). Claudin-4 immunohistochemistry was also evaluated quantitatively using preserved (n = 29; R/RS = 20 and D/T = 9; 2009–2021) and fresh HD specimens for comparison with anorectal malformation patients having colostomy closure as controls (n = 42) and between HD-A versus HD-N, R/RS versus D/T, and HAEC (+) versus HAEC (−). Technically inadequate or transitional zone PT were excluded. Subjects were 123 PT cases. Mean ages at PT/colostomy closure (years) were R/RS: 2.7 ± 2.9, D/T: 1.6 ± 2.2, and controls: 1.4 ± 0.7. Postoperative HAEC occurred 18 times in 14 PT cases (grade I = 5, grade II = 13). Post-PT HAEC was significantly more frequent in D/T (50.0% versus 6.4%; p < 0.001); Claudin-4 was significantly lower in HD-N from post-PT HAEC cases, especially D/T (p < 0.05) on immunohistochemistry. Claudin-4 was significantly lower in HD-N/HD-A compared with controls on immunoblotting (p < 0.05) and immunohistochemistry (p < 0.001). qPCR showed TJP-1, TJP-2, JAM-1, JAM-2, Claudin-4, and BLT-2 were significantly lower in HD-N/HD-A compared with controls. Lower Claudin-4 and BLT2 in post-PT HAEC HD-N (especially D/T) suggests generalized epithelial barrier derangement with possible etiologic implications for HAEC. Ⅱ